Namibia's Minister of Education Receives PhD at AeU - Leong, Irene (The Sun, 2014)
At AeU's 4th Convocation, Dr David Richard Namwandi was conferred a PhD, in which he studied the reasons behind the failure to implement the Southern African Development Community Protocol on Education and Training.